2018
DOI: 10.1111/nhs.12394
|View full text |Cite
|
Sign up to set email alerts
|

Taste, choice and timing: Investigating resident and carer preferences for meals in aged care homes

Abstract: There has been little empirical investigation of the preferences of people living in aged care homes for food services. The aim of the present study was to elicit consumer preferences and their willingness to pay for food service in aged care homes. Current residents or their family members were invited to take part in the discrete choice experiment questionnaire administered via interview. Of the 109 eligible residents and 175 eligible family members approached for consent 121 (43%) participated, including 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…This study identified multiple environmental barriers that are consistent with previous reports, suggesting that an unsupportive dinning environment negatively impacts mealtime care in residential care settings (Chaudhury, Hung, & Badger, 2013). Multiple complaints from staff in relation to the dining environment, including overstimulation and poorly tasting food were discussed previously (Milte, Ratcliffe, Chen, Miller, & Crotty, 2018). Varied environmental modifications that manipulate meal appearance and quality, physical environment elements, and dining routines have been tested and demonstrate inconsistent evidence in improving eating performance and intake (Abbott et al., 2013; Bunn et al., 2016; Liu et al., 2014; Poscia et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…This study identified multiple environmental barriers that are consistent with previous reports, suggesting that an unsupportive dinning environment negatively impacts mealtime care in residential care settings (Chaudhury, Hung, & Badger, 2013). Multiple complaints from staff in relation to the dining environment, including overstimulation and poorly tasting food were discussed previously (Milte, Ratcliffe, Chen, Miller, & Crotty, 2018). Varied environmental modifications that manipulate meal appearance and quality, physical environment elements, and dining routines have been tested and demonstrate inconsistent evidence in improving eating performance and intake (Abbott et al., 2013; Bunn et al., 2016; Liu et al., 2014; Poscia et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…While DCEs have been predominantly used in health economics for primary care treatment [12][13][14][15], their potential for use within the context of nutrition research is becoming increasingly recognised [9,[16][17][18][19][20][21][22]. DCEs offer an opportunity to identify the most important influences on meal-based eating decisions that should be targeted to improve dietary interventions and policies in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…DCEs offer an opportunity to identify the most important influences on meal-based eating decisions that should be targeted to improve dietary interventions and policies in young adults. However, DCE research on meal choices to date has focused on middle to older adults [ 19 , 23 ], parents [ 22 ] and children [ 20 ]. To our knowledge, only one DCE has been undertaken in young adults, which focused on snacking behaviours in college students [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although scarcely researched in this context, previous studies have found choice and autonomy in the institutional food experience to be related to enhanced motivation to consume meals, food satisfaction and well-being [ 57 , 58 , 59 ]. Most of the informants in this study (particularly the younger part of the sample) stressed the importance of expectations related to freedom of choice and were aware that it is not the norm in nursing homes today.…”
Section: Findings and Discussionmentioning
confidence: 99%